Familial Pulmonary Alveolar Microlithiasis: A Rare Case Report with Emphasis on Imaging Findings - AL-Timimy, Qays Ahmed Hassan; asghar, Abdullateef Ali; Alassal, Muthanna D,R. (AL-Kindy College Medical Journal, 2015)
ABSTRACT Pulmonary alveolar microlithiasis is rare infiltrative pulmonary disease characterized by intra-alveoli deposition of microliths. We present a familial case of an adult female with complaint of progressive shortness of breath on exertion. Chest radiograph showed innumerable tiny dense nodules, diffusely involving both lungs mainly the lower zones. High-resolution CT scan illustrated widespread intra-alveolar microliths, diffuse ground-glass attenuation areas and septal thickening predominantly in the basal regions. Chest radiograph is all that is needed for the diagnosis of this case but CT scan was done to demonstrate the extent and severity of this disease